Differential Shape of Geminivirus Mutant Spectra Across Cultivated and Wild Hosts With Invariant Viral Consensus Sequences - Sánchez-Campos, Sonia; Domínguez-Huerta, Guillermo; Díaz-Martínez, Luis; Tomás, Diego M.; Navas-Castillo, Jesús; Moriones, Enrique; Grande-Pérez, Ana (Frontiers in Plant Science, 2018)
Geminiviruses (family Geminiviridae) possess single-stranded circular DNA genomes that are replicated by cellular polymerases in plant host cell nuclei. In their hosts, geminivirus populations behave as ensembles of mutant and recombinant genomes, known as viral quasispecies. This favors the emergence of new geminiviruses with altered host range, facilitating new or more severe diseases or overcoming resistance traits. In warm and temperate areas several whitefly-transmitted geminiviruses of the genus Begomovirus cause the tomato yellow leaf curl disease (TYLCD) with significant economic consequences. TYLCD is frequently controlled in commercial tomatoes by using the dominant Ty-1 resistance gene. Over a 45 day period we have studied the diversification of three begomoviruses causing TYLCD: tomato yellow leaf curl virus (TYLCV), tomato yellow leaf curl Sardinia virus (TYLCSV) and tomato yellow leaf curl Malaga virus (TYLCMaV, a natural recombinant between TYLCV and TYLCSV). Viral quasispecies resulting from inoculation of geminivirus infectious clones were examined in plants of susceptible tomato (ty-1/ty-1), heterozygous resistant tomato (Ty-1/ty-1), common bean, and the wild reservoir Solanum nigrum. Differences in virus fitness across hosts were observed while viral consensus sequences remained invariant. However, the complexity and heterogeneity of the quasispecies were high, especially in common bean and the wild host. Interestingly, the presence or absence of the Ty-1 allele in tomato did not lead to differences in begomovirus mutant spectra. However, the fitness decrease of TYLCSV and TYLCV in tomato at 45 dpi might be related to an increase in CP (coat protein) mutation frequency. In Solanum nigrum the recombinant TYLCMaV, which showed lower fitness than TYLCSV, at 45 dpi actively explored Rep (replication associated protein) ORF but not the overlapping C4. Our results underline the importance of begomovirus mutant spectra during infections. This is especially relevant in the wild reservoir of the viruses, which has the potential to maintain highly diverse mutant spectra without modifying their consensus sequences.